PROFIL PENYANDANG EPILEPSI DI POLIKLINIK SARAF RSUP PROF. DR. R.D. KANDOU MANADO PERIODE JUNI 2013 – MEI 2014 - Khasanah, Rhiza; Mahama, Corry N.; Runtuwene, Theresia (e-CliniC, 2015)
Abstract: Epilepsy is one of the oldest neurological diseases, found in all ages, and can cause impairment and mortality. Epilepsy is still a major public health problem, not only because of its health implications but also for its connotations in social, cultural, psychological, and economic life. This study aimed to obtain a description of patients with epilepsy in Neurology Clinic of Prof. Dr. RD Kandou Manado General Hospital, period of June 2013 - May 2014. The method used in this study was descriptive retrospective. The results showed that the number of epileptic patients was higher in males than in females. By the age group age, it was found that epileptic patients in young adult age group were the most frequent. By the level of education, it was found that patients with epilepsy were more common high school graduated. By the type of work; it was found that a lot of patients with epilepsy had no ocuupation yet and were still students/college students. Patients with partial seizure type (focal) epilepsy were the most commonly found. By past medical history, it was found that most patients had experienced seizures. The most common treatment for epileptic patients was monotherapy antiepileptic drugs.. Keywords: epilepsy, seizure Abstrak: Epilepsi adalah salah satu penyakit neurologi tertua, ditemukan pada semua umur dan dapat menyebabkan hendaya serta mortalitas. Epilepsi masih menjadi masalah kesehatan masyarakat yang utama, bukan hanya karena implikasi kesehatan tetapi juga untuk konotasi sosial, budaya, psikologis dan ekonomi. Penelitian ini bertujuan untuk memperoleh gambaran penyandang epilepsi di Poliklinik Saraf RSUP Prof. DR. R. D. Kandou Manado periode Juni 2013 – Mei 2014. Penelitian ini bersifat deskriptif retrospektif. Hasil penelitian menunjukkan penyandang epilepsi laki-laki lebih banyak dibandingkan dengan perempuan. Berdasarkan golongan usia, terbanyak ditemukan pada golongan usia dewasa muda. Berdasarkan tingkat pendidikan, terbanyak ditemukan pada lulusan SMA. Dilihat dari jenis pekerjaannya, banyak penyandang epilepsi yang belum bekerja dan masih berstatus sebagai pelajar/mahasiswa. Penyandang epilepsi dengan jenis bangkitan parsial (fokal) paling banyak ditemukan dari pada penyandang epilepsi dengan jenis bangkitan umum. Berdasarkan riwayat penyakit dahulu terbanyak terdapat pada riwayat penyakit dahulu dengan kejang. Pengobatan tersering yang dilakukan terhadap penyandang epilepsi ialah dengan monoterapi obat-obat anti epilepsi. Kata kunci: epilepsi, kejang